Experiencia en el rediseño curricular del programa en contaduría pública y alta dirección: una visión de la profesión contable hacia la tercera década del siglo XXI (2016)
This paper has been developed in order to share the experience at Universidad Popular Autónoma del Estado de Puebla during the redesign process of its academic program entitled Licenciatura en Contaduría y Alta Dirección (Bachelor´s Degree in Accounting and Senior Management). This redesign process required to identify essential features according to the profile required by qualified accounting academic degree programs in Puebla, México and Latin-American universities. Also, this redesigned curriculum takes into account the competences required by the professional accountants at international level and considering the social needs atlocal and regional level required for this profession. This redesign of the related academic program also promotes that the student becomes able to develop the basic and professional skills of the accounting discipline in order to efficiently respond to the needs required by society in a context of constant change. This academic program allows the student to become to a professional accountant well prepared to succeed in an economy with encouraging prospects and opportunities for the coming decades: Mexico.